Effects of a low-volume plyometric training in anaerobic performance of adolescent athletes - Assuncao, A. R.; Bottaro, M.; Cardoso, E. A.; Dantas da Silva, D. P.; Ferraz, M.; Vieira, C. A.; Gentil, P. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Parameters related to the anaerobic capacity and power may be important for the performance of many sports whose skills are related to high-intensity and short-duration efforts. Although plyometric training (PT) has been widely used in the regular strength and conditioning programs of young athletes, its effects on anaerobic performance are still controversial. Therefore, the purpose of the present study was to evaluate the effects of PT in anaerobic performance in young athletes. METHODS: Twenty-nine adolescent athletes participated in this 10-week study. Baseline and post intervention testing included Flying Start 30 m Sprint Test (F30), 1600 m, and Running-based Anaerobic Sprint Test (RAST). Subjects were divided in two groups: one completed only their regular training sessions, thus serving as the control (CON, N.=15), whereas the other performed the regular training plus twice-weekly low-volume plyometric training (PLYO, N.=14). RESULTS: PLYO groups had significant increases in all variables analyzed. The novel findings were the increase in F30 performance (4.22% for PLYO vs. 1.08% for CON), the decreases in Fatigue Index (9.9% for PLYO vs. 1.53% for CON), and increases in minimum (19.41% for PLYO vs. 0.29 for CON), mean (14.7% for PLYO vs. 0.16% for CON) and peak power (10.88% for PLYO vs. 0.81% for CON) during the RAST Test. CONCLUSIONS: Considering that anaerobic performance is an important feature in many sports, our results suggests that coaches involved with strength and conditioning of youth athletes should consider the inclusion PT in their training periodization.